Enhancing Vocabulary Mastery Through Bamboozle Games: A Study on Second-Year Students of SMP Negeri 1 Bandar Seikijang - Angellika; Novitri; Mahdum (IKIP Siliwangi, 2026)
This research investigated the effectiveness of Bamboozle games, an online game-based learning platform, in improving students’ vocabulary mastery. This research employed a pre-experimental design utilizing a one group pre-test post-test. The respondents of this research were eighth-grade students at SMP Negeri 1 Bandar Seikijang, with 29 students selected through cluster random sampling. The instrument consisted of a 30 item multiple choice vocabulary test. The data were analyzed using SPSS 30 including normality testing, paired sample t-test, N-Gain score, and effect size. The result found there is an increase in scores from the pre-test to the post-test. The mean score was 62.86 in the pre-test and 77.83 in the post-test with N-Gain score in the medium category (0.44). The effect size Cohen’s d demonstrated a strong practical effect. In conclusion, Bamboozle effectively enhances vocabulary mastery and can be applied as a supportive digital tool in English language teaching.